Technology development to evaluate the effectiveness of viscosity reducing excipients - Banik, Niels; Braun, Stefan; Brandenburg, Jan Gerit; Fricker, Gert; Kalonia, Devendra S.; Rosenkranz, Tobias (International journal of pharmaceutics, 2022)
Addition of pharmaceutical excipients is a commonly used approach to decrease the viscosity of highly concentrated protein formulations, which otherwise could not be subcutaneously injected or processed. The variety of protein-protein interactions, which are responsible for increased viscosities, makes a portfolio approach necessary. Screening of several excipients to develop such a portfolio is time and money consuming in industrial settings. Responsible protein-protein interactions were investigated using the interaction parameter kD obtained from dynamic light scattering measurements in the studies presented herein. Together with in-silico calculated excipient parameter, kD could be used as a screening tool accelerating screening and formulation development as kD is suitable to high-throughput formats using small quantities of protein and low concentrations. A qualitative correlation between kD and high-concentration viscosity behavior could be shown in our case.
Gesehen am 07.12.2022